2008
DOI: 10.1002/jbm.a.31744
|View full text |Cite
|
Sign up to set email alerts
|

Nano hydroxyapatite structures influence early bone formation

Abstract: In a study model that aims to evaluate the effect of nanotopography on bone formation, micrometer structures known to alter bone formation, should be removed. Electropolished titanium implants were prepared to obtain a surface topography in the absence of micro structures, thereafter the implants were divided in two groups. The test group was modified with nanosize hydroxyapatite particles; the other group was left uncoated and served as control for the experiment. Topographical evaluation demonstrated increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
4
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 40 publications
6
154
4
10
Order By: Relevance
“…These AM implants likewise demonstrated substantial bone ongrowth and ingrowth to their porous surfaces, with additional bone through growth in the cores. Although similar HA coatings have previously demonstrated a beneficial effect on non-porous titanium surfaces or inert structures, such as PEEK, 26,27 the current study showed that the dip, spin, heat treated nanocrystalline HA coating did not further enhance results compared to uncoated AM implants. The addition of autograft, on the other hand, resulted in significantly increased bone ingrowth and through growth within the AM implant, potentially further promoting osteointegration.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…These AM implants likewise demonstrated substantial bone ongrowth and ingrowth to their porous surfaces, with additional bone through growth in the cores. Although similar HA coatings have previously demonstrated a beneficial effect on non-porous titanium surfaces or inert structures, such as PEEK, 26,27 the current study showed that the dip, spin, heat treated nanocrystalline HA coating did not further enhance results compared to uncoated AM implants. The addition of autograft, on the other hand, resulted in significantly increased bone ingrowth and through growth within the AM implant, potentially further promoting osteointegration.…”
Section: Discussioncontrasting
confidence: 62%
“…For AM+HA implants, a ~20nm layer of HA was applied to implant surfaces using a dip-coating precipitate technique as previously described. 26,27 AM+Auto implants are described in the Animal Model section below. All implants were gamma-sterilized prior to use.…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications of the atomic composition of the surface have led to significant improvements in the cell response on the surface material both in vitro and in vivo [10][11][12][13] . Impregnation or coating with hydroxyapatite 14,15) or calcium phosphate 16,17) have been proposed as biomimetic approaches. However, despite the success achieved through surface chemistry modifications in the early host-implant integration, there is a general consensus that the modulation of surface texturing is also an important and desirable variable, regardless of the surface chemistry approach followed in endosseous implants 18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) and other calcium phosphate materials have been indicated in cases in which the optimal surgical fit is not achievable during surgery, and the HA surface properties may enhance bone filling of the defect area 6 . The biological properties of the synthetic hydroxyapatite are well documented in literature, and it has been used for correcting bone defects in human beings and in other species 7 .…”
Section: Introductionmentioning
confidence: 99%